2015
DOI: 10.1161/strokeaha.115.008582
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline Reduces Spontaneous Hemorrhage in Mouse Models of Cerebral Amyloid Angiopathy

Abstract: Background and Purpose Cerebral Amyloid Angiopathy (CAA) is a common cause of recurrent intracerebral hemorrhage (ICH) in the elderly. Previous studies have shown that CAA induces inflammation and expression of matrix metalloproteinase-2 and -9 (gelatinases) in amyloid-laden vessels. Here, we inhibited both using minocycline in CAA mouse models to determine if spontaneous ICH could be reduced. Methods Tg2576 (n=16) and 5×FAD/ApoE4 knock-in mice (n=16), aged to 17 and 12 months, respectively, were treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 60 publications
0
25
0
1
Order By: Relevance
“…There are several new CypA inhibitors recently developed and investigated for use against hepatitis-C and HIV infections including CPI-431-32 [197], compound 25 [198], SCY-635 [199] and MM284 [200], which all may have a potential to stabilize the BBB in APOE4 carriers. In addition to CypA inhibitors, there are a number of identified MMP-9 inhibitors including minocycline [201], curcumin [202], SB-3CT(2) [203] and compound 18 [204]. For example, minocycline has been demonstrated to reduce hemorrhage frequency and increase endothelial tight junction and basement membrane proteins in aged 5xFAD/ APOE4 transgenic mice [201].…”
Section: Vasculoprotective Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several new CypA inhibitors recently developed and investigated for use against hepatitis-C and HIV infections including CPI-431-32 [197], compound 25 [198], SCY-635 [199] and MM284 [200], which all may have a potential to stabilize the BBB in APOE4 carriers. In addition to CypA inhibitors, there are a number of identified MMP-9 inhibitors including minocycline [201], curcumin [202], SB-3CT(2) [203] and compound 18 [204]. For example, minocycline has been demonstrated to reduce hemorrhage frequency and increase endothelial tight junction and basement membrane proteins in aged 5xFAD/ APOE4 transgenic mice [201].…”
Section: Vasculoprotective Approachesmentioning
confidence: 99%
“…In addition to CypA inhibitors, there are a number of identified MMP-9 inhibitors including minocycline [201], curcumin [202], SB-3CT(2) [203] and compound 18 [204]. For example, minocycline has been demonstrated to reduce hemorrhage frequency and increase endothelial tight junction and basement membrane proteins in aged 5xFAD/ APOE4 transgenic mice [201]. Furthermore, recent studies showed that minocycline significantly reduced the infarct size, prevented tissue loss, improved perfusion, reduced BBB permeability, and increased tight junction protein levels in spontaneously hypertensive stroke-prone rats [205,206].…”
Section: Vasculoprotective Approachesmentioning
confidence: 99%
“…The minocycline hugely modified the MMP and inflammatory pathways in a positive way and connecting to that, higher levels of microvascular tight junction and basal lamina proteins were found, proving its BBB protective effect, which could be utilized in ischemic stroke treatment, parallel to rtPA administration [157]. Furthermore, minocyclin was tested on spontaneous hypertensive rats as well.…”
Section: Minocyclinmentioning
confidence: 88%
“…Caspase-1, caspase-3, cyclo-oxygenase-2, inducible nitric oxide synthase, p38 mitogenactivated protein kinase, gelatinase, MMP-9 are supposed to participate in the molecular mechanism of minocycline [157,160].…”
Section: Minocyclinmentioning
confidence: 99%
“…Son dönemde fareler üzerinde yapılan bir çalışmada SAA'da minosiklinin, gliyozisi ve enflamatuvar gen ekspresyonunu azalttığı gösterilmiştir. Ayrıca, minosiklin ile tedavi edilen farelerde mikrovasküler sıkı bağlantıların "tight junction" ve bazal lamina proteinlerinin arttığı saptanmış olmakla birlikte, SAA ilişkili beyin kanamalarını önlemedeki etkinliğinin klinik çalışmalarla desteklenmesi gereklidir [47] .…”
Section: Nöroprotektif Etkiunclassified